2003
DOI: 10.1038/sj.ejcn.1601502
|View full text |Cite
|
Sign up to set email alerts
|

Associations between reproduction and maternal body weight: examining the component parts of a full reproductive cycle

Abstract: Objective: Many transitional societies currently face both extremes of nutritional status, undernutrition and overnutrition. Women of reproductive age are at high risk of these conditions. The purpose of this review is to consider evidence for relationships between reproduction and nutritional status in women from societies of varying economic development, using body weight or weight-for-height as indicators of maternal nutritional status. Design: The conceptual framework guiding this review is that the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 114 publications
(141 reference statements)
2
25
0
Order By: Relevance
“…While parity-related increases in maternal weight are often observed in well-nourished women (27,28), depletion of maternal energy reserves may result from limited dietary intake and high levels of reproductive stress in women from lower income countries (27,29,30). We observed that while higher parity was related to higher weight, a greater number of months pregnant and lactating in each interval related to lower body weight, consistent with the high energy demands of these reproductive stresses.…”
Section: Figuresupporting
confidence: 83%
“…While parity-related increases in maternal weight are often observed in well-nourished women (27,28), depletion of maternal energy reserves may result from limited dietary intake and high levels of reproductive stress in women from lower income countries (27,29,30). We observed that while higher parity was related to higher weight, a greater number of months pregnant and lactating in each interval related to lower body weight, consistent with the high energy demands of these reproductive stresses.…”
Section: Figuresupporting
confidence: 83%
“…The implicit assumption, therefore, is that the "postnatal" and "prenatal" maternal and paternal BMI are strongly correlated. 48 Women in less affluent societies have been shown to retain less weight with each pregnancy, 49 although the evidence for maternal weight loss as a result of their prepregnancy undernutrition remains unclear. Overlapping of closely spaced pregnancies with the lactation period, however, could lead to loss of maternal body weight.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Excessive gestational weight gain and the inability to lose this weight in the postpartum period are thought to be two of the main ways in which reproduction contributes to overweight. 4,5,[8][9][10] In developing countries, frequent reproductive cycles (especially when accompanied by short or absent recuperative intervals, that is periods free from pregnancy or breastfeeding) have been suggested as a risk factor for maternal depletion. 11 Poor dietary intake and heavy activity patterns further exacerbate the nutritional and energetic stress of frequent reproductive cycles, such that nutritional status deteriorates over time.…”
Section: Introductionmentioning
confidence: 99%